TRANSFUSION ASSOCIATED GRAFT VERSUS HOST DISEASE - Anwar, Masood; Bhatti, Farhat Abbas (Journal of Ayub Medical College Abbottabad, 2003)
Transfusion associated graft versus host disease (TA-GVHD) results from engraftment of viable donor T-lymphocytes in recipient that can not recognize or destroy them. It is seen in immunocompromised patients and pre-mature neonates. It can also occur in immunocompetent individuals receiving blood from first-degree relatives. It has emerged as single most common cause of death resulting from transfusion. Patients with B-cell malignancies appear to be especially at risk. TA-GVHD is associated with 80-90% mortality. Death most commonly occurs due to infection or haemorrhage secondary to pancytopenia. It is therefore important to prevent its occurrence. Prevention can be achieved either by complete removal of T-lymphocytes from donors blood or by abolishing their proliferating potentials. Available methods of leuko-depletion are not effective in preventing TA-GVHD. Only effective way is to inactivate T-lymhocytes. This can be achieved by irradiating blood product with gamma or X-ray irradiation. The concerns about malignant transformation of cells or reactivation of intracellular viruses have not been proved so far. Newer technologies for T-cell inactivation, which are not based on irradiation, are currently under trial. Key words: Transfusion hazards, TA-GVHD, Graft versus Host Disease, Blood product irradiation, Transfusion to immunocompromised, Transfusion from first degree relatives